Use of the Martius advancement flap for low rectovaginal fistulas. (15th July 2019) - Trompetto, M.; Realis Luc, A.; Novelli, E.; Tutino, R.; Clerico, G.; Gallo, G.
Abstract: Aim: The percentage recurrence after any surgical treatment for low rectovaginal fistula (LRVF) is unacceptably high. The aim of this study was to evaluate the short‐ and long‐term results of the Martius procedure in a carefully selected series of patients with a LRVF of at least 1 cm diameter who had had at least two previous surgeries or in the presence of chronically inflamed local tissues. Method: Between January 2009 and April 2017, 24 patients with the abovementioned features were prospectively included in this study. Success was defined both as the absence of any subjective symptoms and the fistula, as confirmed by evaluation under anaesthesia. Postoperative complications were assessed using the Clavien–Dindo classification. Quality of life (SF‐12 score), quality of sexual life [Female Sexual Function Index (FSFI) score] and continence [Cleveland Clinic Incontinence Score (CCIS)] were also determined pre‐ and postoperatively. Results: The mean follow‐up was 42 ± 29 months (range 3–101 months). The overall success rate was 91.3% (22/24 patients). The median operation time was 50 min (range 45–70 min), and the median hospital stay was 3.5 days (range 3–5 days). No major complications occurred. Pre‐ and postoperative CCIS did not differ [1 (range 0–3.5)]. The postoperative SF‐12 score improved both in terms of the physical (33.6 ± 7.2 vs 50.8 ± 7.8; P < 0.001) and mental (32.6 ± 6.7 vs 56.3 ± 7.8; P < 0.001) components. FSFI improved from 19.5 ± 6.6 to 24.4 ± 6.3 ( P < 0.001). Conclusion: The Martius procedure should be considered as the first‐line method of treatment in carefully selected cases of LRVF.